Pengaruh pola agihan hujan terhadap hidrograf satuan. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Kawasan dan Pedesaan Universitas Gadjah Mada, 1999)
ABSTRACT The unit hidrograph method is one of the flood estimation methods commonly used for design flood estimation in Indonesia. A number of problems emerges in the application of the unit hydrograph such as determination rainfall pattern used both for unit hydrograph derivation as well as for design. This problem happened since rainfall pattern as natural phenomenon occurs randomly, time invariant and due to lack of automatic rainfall data. A number of rainfall patterns such as Tadashi Tanimoto, ECI, Alternating Block Method, and a rainfall pattern that based on automatic rainfall data are used for deriving unit hydrograph for a number flood events. Results show that Alternating Block Method gives a better results with relatively small bias than others compare with unit hydrograph derived based on automatic data.